(untitled) (Applied Biological Research, 2024)
Johne’s disease in ruminants is caused by Mycobacterium avium paratuberculosis (MAP), which has been linked to inflammatory bowel disease and Crohn’s disease in humans. Milk from infected ruminants is considered the primary source of transmission. This study aimed to estimate the presence of MAP in clinical samples (blood and serum) from confirmed thyroid and arthritis cases. Samples were collected from the Community Healthcare Center, Bhangel campus, Noida NCR region, India.A total of 111 blood samples (76 thyroid and 35 arthritis) were collected and analyzed using IS900 blood PCR, indigenous ELISA, and TaqMan probe qPCR IS1311 PCR_REA. Among the serum samples, 19 (17.1%) tested positive for MAP antibodies via ELISA (thyroid: 18.4%; arthritis: 14.2%). For the blood samples, MAP was detected in 10.8% and 11.7% of cases using IS900 PCR and TaqMan probe qPCR, respectively.The bio-incidence of MAP in thyroid patients ranged from 9.2–14.2%, while in arthritis patients it ranged from 10.5–14.2%, as determined by IS900 PCR and TaqMan probe qPCR. A substantial agreement was observed between ELISA and PCR results. Molecular strain typing using IS1311 PCR_REA identified the prevalent biotype as the ‘Indian Bison type.’This study suggests moderate exposure of the human population to MAP in the Noida NCR region. The presence of the ‘Indian Bison type’ biotype indicates a potential zoonotic transmission pathway from cattle products to humans. To validate these findings, further research with larger cohorts of thyroid and arthritis patients is recommended.